Workshop Pengembangan Inovasi Pendidikan Prasekolah Berbasis Mastery Progresif - Wulandari, Retno Tri; Rahayuningtyas, Wida; Yafie, Evania; Anisa, Nur (Universitas Negeri Malang, 2023)
One sign of success in school management can be seen in its ability to develop activity programs for the continuity of the student learning process. The development of a progressive mastery-based activity program is one model of school programming. The use of the andragogy learning approach in the training process with the pair and sharing method through question and answer activities, discussions, practice preparation and program implementation assistance to result in increased insight and ability of trainees in compiling and implementing Progressive Mastery-based school activity programs in schools. The conclusion is that the ability of PAUD teachers to arrange Progressive Mastery-based activity programs has increased after attending the workshop.Salah satu tanda keberhasilan dalam pengelolaan sekolah tampak pada kemampuannya dalam mengembangkan program kegiatan bagi keberlangsungan proses belajar siswa. Pengembangan program kegiatan berbasis mastery progresif adalah salah satu model penyusunan program sekolah. Penggunaan pendekatan pembelajaran andragogy dalam proses pelatihan dengan metode pair and sharing melalui aktivitas tanya jawab, diskusi, praktik penyusunan dan pendampingan pelaksanaan program hingga mengahasilkan peningkatan wawasan dan kemampuan peserta pelatihan dalam menyusun dan mengimplementasikan program kegiatan sekolah berbasis mastery progresif di sekolah. Kesimpulan yang diperoleh bahwasannya kemampuan guru PAUD menyusun program kegiatan berbasis mastery progresif meningkat setelah mengikuti workshop.